Childhood maltreatment and sleep in children and adolescents: A systematic review and meta-analysis. (June 2022) - Schønning, Viktor; Sivertsen, Børge; Hysing, Mari; Dovran, Anders; Askeland, Kristin G.
Summary: Childhood maltreatment is a global problem with the risk of serious health consequences for children and adolescents, including sleep problems. Former systematic reviews have examined the association between childhood maltreatment and sleep problems in adults, but no systematic review has investigated the literature on childhood maltreatment and sleep problems in childhood and adolescence. We published a protocol (PROSPERO: CRD42021225741) and conducted a systematic literature search using nine electronic databases. Upon duplicate removal, 1530 records were screened against the inclusion criteria, and 26 studies were included in the review. The most studied sleep outcomes were symptoms of insomnia, sleep duration and nightmares. The results showed significant associations between exposure to childhood maltreatment and insomnia symptoms (OR 3.91, 95%CI: 2.64–5.79, p < .001), shorter sleep duration (−12.1 min, 95%CI: −19.4 to −4.7, p < .001) and nightmares (OR 3.15, 95%CI: 2.38–4.18, p < 001). There was a considerable heterogeneity in measures and instruments used to examine sleep and maltreatment. Our findings highlight the importance of screening and intervening for sleep problems in children and adolescents exposed to childhood maltreatment.